The Relationships between Learning Orientation, Subjective Norm and Entrepreneurial Intention among the Undergraduate Students in Malaysia - U., N. Saraih; M., A. Ali; M., S.Z. Mohd Sufian; R. , Ibnu Ruslan (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to examine the relationship between learning orientation and subjective norm towards entrepreneurial intention among undergraduate students in one of the public universities in Malaysia. The data is analyzed through a survey (questionnaire) from 488 undergraduate students in one of the public universities in the Northern Region of Malaysia. Hypotheses for all direct effects between the predictors (e.g., learning orientation and subjective norm) and criterion (entrepreneurial intention) are tested using regression analysis. Results presented that students in this university have a high level of entrepreneurial intention (µ = 3.64), learning orientation (µ = .75), and subjective norm (µ = .47). Also, positive associations are found between students’ entrepreneurial intention and learning orientation (r=.49, p=.00) and subjective norm (r=.63, p=.00). Practical implications of the results are discussed. Last but not least, several suggestions for the institution to increase the level of students’ learning orientation and subjective norm have also been touched.